Entrepreneurship in the Society of Spectacle: Soccer Management in a Globalized World (Global Journal of Management and Business Research, 2014)
The arising of business globalization in recent decades changed the market of symbolic goods, in the soccer field, in a billionaire and complex business. These factors led to radical changes in the form of consumption of this sport, which generated a great increase in revenues to the teams, grounded in marketing models of major European leagues. Through descriptive research, ex-post-factum, using the technique of in-depth interviews with managers and project participants for subsequent content analysis, this research sought to identify the strategies employed to value the Corinthians brand (soccer team from São Paulo, Brazil)in a perspective of business strategy. The survey results, point out the importance of entrepreneurial vision to explore the valuable, rare, inimitable and irreplaceable resources present in VRIO model, as stated by the Resources Business View (RBV) theory, to achieve differentiated positioning. Limitations of the research are in proper character of the phenomenological method that favors the rescue of "original speech" of the project participants as it was done in this case. So it is not recommended one could make generalizations of the results presented, although it represents a significant and real context of soccer business in Brazil.
Keywords: entrepreneurship; innovation soccer management; equity brand